APLIKASI MESIN PENCARI FILE MEMANFAATKAN API WEB SERVICE 4SHARED (Information Technology and Telematics, 2014)
AbstractAdvances in computer technology in all fields of science indaily life does have a significant role. Computers typically usedto produce or make some information.The purpose of this study is to produce applications that areused to search and download files and providing advice in theform of mp3 files last uploads by other users in web service4shared. To do a file search, the system is split into severalcategories. that will allow a user to search the desired file.The results of the analysis and discussion of data retrieval bymeans accessed and updated using the POST method, utilizingthe function of the API at 4shared with converting XML into anobject that can be processed with normal property selectorsand array iterators through Simplexml_load_file function.Keywords: System Development, 4shared APIutilization, file search engine, the Web Service